FEMINITIVES IN THE MODERN UKRAINIAN LANGUAGE: PSYCHOLINGUISTIC ASPECT - GAPCHENKO, Olena (Linguistic and Conceptual Worldviews, 2025)
Backgraund. The study presents a psycholinguistic analysis of the functioning of femininities in the modern Ukrainian language. The relevance of the topic is due to the growing public attention to the linguistic representation of gender equality, the increasing frequency of femininities in public discourse and the insufficient level of their psycholinguistic understanding. The object of the study is the nominations of women by profession, social status and field of activity. The aim is to outline the psycholinguistic specifics of perception, comprehension and use of feminine gender in the speech of modern Ukrainian speakers. Objectives: to describe the semantic characteristics of feminitives, to establish the peculiarities of associative perception of feminine lexemes, to find out the linguistic and extra-linguistic factors that influence the choice of the relevant nominations, to characterise the role of feminitives in a native speaker’s lexicon. Methods: descriptive, contextual and semantic, morphological, communicative and pragmatic analysis; free associative experiment. Results. The study examines the history of the formation of the feminitive subsystem of the Ukrainian language, the types of word-formation models and the degree of their normativity. Using an associative experiment, it is analysed the reactions of native speakers to a number of feminitive units selected from contemporary media discourse. It has been found that the psychologically real meaning of these units is formed at the intersection of the speaker’s linguistic, cognitive and socio-cultural competences. A significant variation of feminitives, pragmatic heterogeneity and different degrees of speakers’ acquisition of the latest nominals are recorded. The influence of age, gender, educational level and regional affiliation on the results of the experiment is traced. Conclusions. The functioning of feminitives in the language of modern Ukrainians reveals active processes of word formation, cultural determinism of language choice and dynamic interaction of collective and individual language consciousness. The psycholinguistic approach allows us to comprehensively understand not only the semantics but also the mental and cognitive nature of feminitives, which reflects the transformation of sociolinguistic norms of modern Ukrainian society.